Workers, the self-employed and TRADEs: Conceptualisation and collective rights in Spain1. Issue 3 (September 2019) - Todolí-Signes, Adrián
The subjective scope of application of Labour Law is set by the Statute of Labour. Nevertheless, the interpretation of the Courts is crucial to understand who is a worker in Spain. In this study, the criteria set by the Spanish courts and their evolution are analysed. Recently, the Spanish Supreme Court seems to have abandoned the 'control test' criteria for classifying workers and has moved towards a personal conceptualisation of work. This paper shows rulings that prove this evolution. Moreover, Spain has its own Self-employed Workers' Statute applicable to common self-employed workers and economically dependent self-employees (TRADEs). In this paper I analyse the concept of both types and the individual and collective rights granted to them by the Self-employed Workers' Statute. Two main conclusions can be drawn: first, the TRADEs are not an intermediate category between employees and self-employees but instead a subcategory of self-employees. Second, the protection granted by the Self-employed Workers' Statute is clearly insufficient.